2006
DOI: 10.1002/gps.1716
|View full text |Cite
|
Sign up to set email alerts
|

The rate of conversion of mild cognitive impairment to dementia: predictive role of depression

Abstract: We conclude that conversion rate from MCI to DSM-IIIR dementia was 21.9% over a period of 3 years. The occurrence of depressive symptoms may constitute a predictor for those who are more likely to progress to dementia. The risk of conversion to dementia was higher among the subjects with an evidence of impairment extending beyond memory than with those who suffered only from memory deficits, and the subjects who converted to dementia in this subtype had significantly higher baseline plasma total homocysteine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(139 citation statements)
references
References 24 publications
8
123
1
7
Order By: Relevance
“…[12][13][14][15] However, the mechanism underlying this relationship remains incompletely understood. In AD, the development of depression may be the consequence of the underlying CNS pathology, namely the selective loss of noradrenergic cells in the locus ceruleus and possibly the serotonergic raphe nuclei.…”
Section: Effect Of Donepezil Treatment In the Nondepressedmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] However, the mechanism underlying this relationship remains incompletely understood. In AD, the development of depression may be the consequence of the underlying CNS pathology, namely the selective loss of noradrenergic cells in the locus ceruleus and possibly the serotonergic raphe nuclei.…”
Section: Effect Of Donepezil Treatment In the Nondepressedmentioning
confidence: 99%
“…Cross-sectional studies indicate that behavioral disturbances are frequently reported in MCI, and the overall pattern of psychopathology is similar to that seen in mild AD, with depression, apathy, anxiety, and irritability among the most commonly exhibited symptoms. [10][11][12] Several longitudinal studies of MCI and normal elderly populations suggest that depression and apathy, in particular, may represent prodromal symptoms of AD that are indicative of subsequent dementia, [12][13][14][15] although not all investigators have confirmed these findings. 16,17 Symptoms of depression were assessed as a secondary outcome measure as part of the Alzheimer's Disease Cooperative Study (ADCS) trial of donepezil (Aricept; Pfizer, New York, NY, and Eisai, Tokyo, Japan), vitamin E, and placebo in patients with MCI.…”
mentioning
confidence: 99%
“…These symptoms are common in subjects with MCI (Apostolova & Cummings, 2007), but it is uncertain whether they can predict AD in this population (Steffens et al 2006). Depressive symptoms were associated with an increased risk of developing AD in some studies (Modrego & Ferrandez, 2004 ;Gabryelewicz et al 2007), and with a decreased risk in others (Rozzini et al 2005 ;Liu et al 2007), while most studies did not find a relationship between depression and AD at all (Tierney et al 1999 ;Visser et al 2000a, b ;Copeland et al 2003 ;Korf et al 2004 ;Robert et al 2006 ;Wang et al 2006 ;Feldman et al 2007 ;Palmer et al 2007 ;Teng et al 2007 ;Panza et al 2008). Similarly, discrepant results have been reported regarding the predictive accuracy of apathy and anxiety for AD (Robert et al 2006 ;Feldman et al 2007 ;Liu et al 2007 ;Palmer et al 2007 ;Teng et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…BACE cleaves APP and releases a large N-terminal fragment (sAPPβ). The membrane-anchored frag- [73,75] Decreased [65] β-amyloid (Aβ) Decreased [45,46] No difference [79][80][81][82] No difference [47] Aβ1- 40 No difference [24] No difference [83] Increased [84] Decreased [85] Aβ1- 42 Decreased [24] Increased [83] -Aβ1-42/Aβ1-40 ratio Decreased [48] No difference [83] Decreased [78,84,86] APP ratio --Decreased [90][91][92][93] Ubiquitin Increased [24] No difference [148] BACE1 Increased [67] --Cholesterol -Decreased [94,95] Increased [96][97][98] 24S-hydroxycholesterol Increased [102] No difference [103] Decreased [104] Homocysteine -Increased [106,107,109] Epidermal growth factor -Decreased [111] Decreased [93] Increased [112] Glial cell line-derived growth factor -Decreased [111] No difference …”
Section: Aβ1-42mentioning
confidence: 99%
“…High Hcy levels in plasma increase the risk for developing AD by two-fold [107] . It has also been shown that controls who develop AD, have higher plasma Hcy levels compared to controls who convert to MCI [108] , and MCI subjects who convert to AD, have higher baseline plasma Hcy levels than stable MCI patients [109] .…”
Section: Cholesterol and 24s-hydroxycholesterolmentioning
confidence: 99%